CMOS-fabricated dielectrophoretic chip with embedded 3D TiN nano-electrode arrays for sperm capture and sperm damage reduction - Liao, I-Hsuan; Shiau, Jeng-Huei; Cheng, Chao-Min (Frontiers in Bioengineering and Biotechnology, 2025)
Introduction:This study developed an embedded 3D TiN nano-electrode arrays with a strong electric field and high biocompatibility for the effective capture of motile sperms. The chip integrates CMOS fabrication technology with a three-dimensional structural design, exhibiting both electrode-based dielectrophoresis and insulator-based dielectrophoresis characteristics. It provides a stable operating environment under strong electric fields with minimal Joule heating interference.Methods:In the experiments, we evaluated the effects of different waveforms and capture spaces on the capture efficiency of boar and bovine sperms.Results and discussionThe results showed that square waves improved capture efficiency by approximately10% and confirmed that the capture space must exceed half the sperm length to enhance efficiency. When operated under a 20 Vpp square wave, the chip only generated a temperature rise of 1.7°C, causing no significant damage to the sperms and no notable decrease in viability. Under optimal conditions, the capture efficiencies for boar and bovine sperms reached 65.54% ± 1.07% and 63.25%, respectively. Overall, the results demonstrate that this chip offers high throughput, low Joule heating interference, and good species adaptability, showing potential for use in dynamic cell capture and high-throughput analysis.